Experience in diagnosis and treatment of pediatric fibular osteomyelitis - Liang, Yuan; Liu, Zhenjiang; Wang, Xin; Ma, Qiang; Hu, Xinyong (Frontiers in Surgery, 2025)
ObjectiveTo summarize and analyze the clinical characteristics, diagnosis, treatment, and prognosis of pediatric fibular osteomyelitis, and to analyze related influencing factors, providing evidence for clinical management of pediatric osteomyelitis in rare locations.MethodsA retrospective analysis was conducted on the clinical data of pediatric patients with fibular osteomyelitis from January 2018 to December 2024, including demographic characteristics, clinical manifestations, laboratory and imaging examinations, microbiological results, treatment modalities, and follow-up outcomes.ResultsA total of 13 patients were included (9 males, 4 females) with a median age of onset of 7.3 years. There were 11 acute cases and 2 chronic cases. The main clinical manifestations were bone pain, fever, and local abscess formation. The positive rate of microbiological culture was 76.9%, with Staphylococcus aureus being the most common pathogen (including 1 case of MRSA). Two patients responded effectively to antibiotic therapy alone, while 11 cases required surgical intervention, including fibular fenestration, debridement, segmental resection, and VSD therapy. All patients showed significant reduction in inflammatory markers after treatment. During 3–24 months of follow-up, 3 cases experienced recurrence requiring repeat surgery, with no severe disability or deformity observed.ConclusionPediatric fibular osteomyelitis has an insidious onset and poses diagnostic challenges. Staphylococcus aureus, particularly MRSA, represents the primary pathogen, with higher rates of surgical intervention and recurrence compared to other long bones. Early accurate diagnosis, adequate antibiotic therapy, and individualized surgical intervention are crucial for improving prognosis.